Sharī’ah Supervisory Boards In Malaysian Islamic Banks Emerging Issues, Challenges, And Responses - Mahmoud Mohamed Ali Mahmoud Edris; Mohamed Sharif Bashir Elsharif; Sidi Mohamed Sidi Ahmed; Hamza Abed Alkarim Hammad (Universiti Sains Islam Malaysia, 2026)
Indexed by MyCite